1994
DOI: 10.1063/1.467161
|View full text |Cite
|
Sign up to set email alerts
|

Bound–bound A 2Σ+–X 2Π transition of NO–Ar van der Waals complexes

Abstract: The bound–bound excitation spectrum of the NO–Ar van der Waals complex associated with the NO A 2Σ+–X 2Π transition has been measured by the resonance enhanced two-photon ionization (RE2PI) method using a time-of-flight (TOF) mass spectrometer. The van der Waals bands characterized by red-shaded rotational contours present no regularity in the progression. The photodissociation action spectra obtained by probing the NO A 2Σ+(v′=0, N′=1–8) products have also been measured, and the binding energies (D0) of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
94
2

Year Published

1994
1994
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(108 citation statements)
references
References 26 publications
12
94
2
Order By: Relevance
“…31 In particular, B3LYP-D3 calculations predicted a minimum energy structure with a Ar-N-O angle of 30 o , whereas high level calculations and experiment find the angle to be 0 o . [45][46][47] A further shallow minimum is predicted for a Ar-N-O angle of 180 o , in agreement with experiment and previous calculations. [45][46][47] This is illustrated in Figure 7 that shows the interaction potential at the B3LYP-D2 level, which closely resembles the B3LYP-D3 one.…”
Section: Variation Of the Dispersion Correctionsupporting
confidence: 89%
See 1 more Smart Citation
“…31 In particular, B3LYP-D3 calculations predicted a minimum energy structure with a Ar-N-O angle of 30 o , whereas high level calculations and experiment find the angle to be 0 o . [45][46][47] A further shallow minimum is predicted for a Ar-N-O angle of 180 o , in agreement with experiment and previous calculations. [45][46][47] This is illustrated in Figure 7 that shows the interaction potential at the B3LYP-D2 level, which closely resembles the B3LYP-D3 one.…”
Section: Variation Of the Dispersion Correctionsupporting
confidence: 89%
“…[45][46][47] A further shallow minimum is predicted for a Ar-N-O angle of 180 o , in agreement with experiment and previous calculations. [45][46][47] This is illustrated in Figure 7 that shows the interaction potential at the B3LYP-D2 level, which closely resembles the B3LYP-D3 one. Also shown is an analogous potential energy surface computed with B3LYP-D2 with modified (increased by a factor of 2 for nitrogen and oxygen) van der Waals radii.…”
Section: Variation Of the Dispersion Correctionsupporting
confidence: 89%
“…The first investigation of the bound-bound à 2 ⌺ ← X 2 ⌸ transition was of quite low resolution but revealed that structure was observable. 7 Subsequent studies with increased resolution 8,9 revealed several bands assignable to vibrational modes. 9 The NO-Ar à − X origin was determined as 44 242.4 cm −1 and this, along with measurements of the dissociation onset, allowed à and X state dissociation energies of 44 and 88 cm −1 , respectively, to be obtained, 8 although, as discussed below, these values have recently been called into question.…”
Section: Introductionmentioning
confidence: 99%
“…7 Subsequent studies with increased resolution 8,9 revealed several bands assignable to vibrational modes. 9 The NO-Ar à − X origin was determined as 44 242.4 cm −1 and this, along with measurements of the dissociation onset, allowed à and X state dissociation energies of 44 and 88 cm −1 , respectively, to be obtained, 8 although, as discussed below, these values have recently been called into question. 10 The identification of the features observed in the bound-bound à − X spectrum was achieved through the enhanced quality of later resonance enhanced multiphoton ionization ͑REMPI͒ experiments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation